Formulation Design and In Vitro Characterization of Etoricoxib Cream for the Treatment of Rheumatoid Arthritis: Formulation Design and In-Vitro Characterization of Etoricoxib Cream for the Treatment of Rheumatoid Arthritis - Muhammad Razi Ullah Khan; Musaddique Hussain; Shahid Masood Raza; Saeed Ur Rashid Nazir; Abrar Ahmed; Sidra Hasnain (Iranian Journal of Pharmaceutical Sciences, 2014)
Non-Steroidal Anti-inflammatory drugs (NSAIDs), including selective cyclooxygenase (COX)-2 inhibitors, have come to play an important role in the pharmacologic management of musculoskeletal disorders. Clinical trials have established the efficacy of etoricoxib in Osteoarthritis, Rheumatoid Arthritis, Acute Gouty Arthritis, Ankylosing Spondylitis, Low back pain, acute postoperative pain, and primary dysmenorrheal. The present research has been undertaken with the aim to develop a novel topical cream formulation of etoricoxib, which would attenuate the gastrointestinal relater toxicities associated with oral administration. Etoricoxib is a highly selective cyclooxygenase‐2 (cox‐2) inhibitor. In the present study, a fixed concentration of Etoricoxib cream (1%) was prepared by using a different combination of Active ingredient and Excipients. To access the efficacy of formulated cream, in vitro evaluation including stability studies, tube extrudes ability, spread ability, pH, viscosity and rheological properties as well as drug diffusion studies were done. After in vitro evaluation of cream formulations, the formulation was evaluated for the anti‐inflammatory and skin irritation study. The results obtained were encouraging and formulation containing Etoricoxib (1%) exhibited the most satisfying results of all the parameters.